Hubungan Pengetahuan dan Sikap Pedagang Hidangan Istimewa Kampung (HIK) Terhadap Kebersihan Diri dan Lingkungan di Kecamatan Kartasura Kabupaten Sukoharjo - Taib, Jamal Ichsan; , Arif Widodo, A.Kep., M.Kes (2017)
Most health problems, in terms of diseases that arise in humans, are caused by unhealthy behavior. Infectious diseases such as tuberculosis and diarrhea are more common in people's behavior less to maintain personal hygiene and environment, so it becomes a breeding ground and source of disease transmission. The purpose of this study are: 1) to describe the knowledge of the special village dish merchant (HIK) on the personal and environmental hygiene in Kartasura District, Sukoharjo Regency, 2) To describe the attitude of the village specialist food merchant (HIK) to the personal hygiene and environment in Kartasura District, Sukoharjo Regency, 3) To analyze The magnitude of the relationship between knowledge with the attitude of a special dish hometown (HIK) against personal hygiene and environment in Kartasura District, Sukoharjo Regency. The research was conducted on 7-9 April 2017 by taking the research location in Kartasura District, Sukoharjo Regency. Total population 139 traders HIK with a sample of 30 respondents. The sampling technique used in this study is Proportional Random Sampling. Chi-Square test results of the relationship between knowledge with personal hygiene and environment obtained X2 value of 29.137 with ρ-value = 0.002. The value of ρ-value is less than 0.05 (0.002 <0.05), whereas in attitude with personal hygiene and environment, the value of X2 is 10,464 with ρ-value = 0,006. The value of ρ-value is less than 0.05 (0.006 <0.05) then it is concluded that Ho is rejected so that there is a relationship between knowledge and attitude with personal hygiene and environment. Keywords: Knowledge, attitude, personal hygiene and environment